Analisis Pengendalian Kualitas Produk Gula Menggunakan Metode Six Sigma di PT PG Candi Baru - Wahyu Kurniawan; Iriani Iriani (Pusat Riset dan Inovasi Nasional, 2024)
The quality of industrial products in Indonesia is currently struggling in terms of product quality control. In ongoing production activities, there are bound to be defects in the product. To reduce this problem in production activities, there are several things that need to be paid attention to. Six Sigma (DMAIC). Six Sigma is a quality improvement program that provides tolerance for defective products and is able to reduce product defects. This data collection was carried out by field observation and interviews with workers and heads. This data collection was carried out by field observations and interviews with workers and heads of KSU Tabek. From the research results, it was found that the total production produced during August - September was 58,088, and 3115 defective products were found. In the sugar production section, PT Madu Baru PG Madukismo had a sigma level of 3.12 with a possible damage of 53,607 per million production (DPMO).